Healthy Design and Urban Planning Strategies framing the SDG 11 Sustainable Cities and Communities. (20th October 2021) - Rebecchi, A; Capolongo, S
Abstract: According to the "Urban Health Rome Declaration" at European meeting "G7 Health" that defines the strategic aspects and actions to improve Public Health into the cities, and referring to the Agenda 2030 in which the 11th SDG argue about "Sustainable Cities and Communities. Make cities and human settlements inclusive, safe, resilient and sustainable", one of the most expressive syntheses of the challenging relationship between urban planning and Public Health is stated by WHO (2016): "Health is the precondition of urban sustainable development and the first priority for urban planners". Referring to the Healthy Cities & Urban Health definitions, we can consider Public Health not merely an aspect of health protection and promotion, but an individual and collective condition, strongly influenced by the environmental context and by the strategies implemented by local Governments. The "Health in All Policies" strategy, clearly underlines how health doesn't depend only on the supply of the healthcare services, but also, on the quality of outdoor and indoor living environments. Aim of the Presentation 3 is the share the findings of a literature review about the link between the urban contexts' morphological and functional features; the results are divided into: 14 Health Outcomes, representing the main Non-Communicable Diseases (NCDs) whose come from the urban environment's quality and by the adoption of healthy lifestyles; 8 types of Environmental Risk Factors (Urban Heat Island Effect; soil/air/acoustic/light pollution; vehicular traffic; Safety & Security; weak attractiveness of places); and 14 Healthy Urban Planning Strategies (green/blue/grey infrastructures; biodiversity protection; adverse meteoric events management; public transport systems; vehicular traffic reduction; pedestrian and cycling paths; social and functional mix; urban solid waste's management; renewable energy and efficiency; outdoor spaces lighting; Design for All).